ERK1/2 in immune signalling - Lucas, Richard M; Luo, Lin; Stow, Jennifer L (Biochemical Society transactions, 2022)
Extracellular signal-related kinases 1 and 2 (ERK1/2) are the final components of the mitogen-activated protein kinase (MAPK) phosphorylation cascade, an integral module in a diverse array of signalling pathways for shaping cell behaviour and fate. More recently, studies have shown that ERK1/2 plays an essential role downstream of immune receptors to elicit inflammatory gene expression in response to infection and cell or tissue damage. Much of this work has studied ERK1/2 activation in Toll-like receptor (TLR) pathways, providing mechanistic insights into its recruitment, compartmentalisation and activation in cells of the innate immune system. In this review, we summarise the typical activation of ERK1/2 in growth factor receptor pathways before discussing its known roles in immune cell signalling with a focus downstream of TLRs. We examine emerging research uncovering evidence of dysfunctional ERK1/2 signalling in inflammatory diseases and discuss the potential therapeutic benefit of targeting ERK1/2 pathways in inflammation.